Integrated metabolomics, transcriptomic, and phytohormonal analyses to study the effects of water stress and foliar abscisic acid application in Thymus species using LC-MS/MS - Alipour, Maryam; Haghighi, Maryam; Rahimmalek, Mehdi; Reichelt, Michael; Martinelli, Laure; Groten, Karin; Mithöfer, Axel (Frontiers in Plant Science, 2025)
Thyme species, including Thymus vulgaris, T. kotschyanus (drought-tolerant) and T. serpyllum (drought-sensitive), are valuable medicinal herbs. They are often grown in arid regions and are increasingly suffering from water stress due to climate change. Here, we analyzed the metabolome and expression of selected genes in leaves of these species under drought stress with and without treatment with the phytohormone abscisic acid (ABA). Among the terpenes, dominant metabolites in thyme, thymol was the most important terpenoid component, followed by thymoquinone, carvacrol and p-cymene in all three species. Drought stress reduced terpene concentrations, while moderate ABA levels increased them. T. kotschyanus showed the highest concentrations of thymol and carvacrol after combined treatment with drought and ABA. Metabolite accumulation was partially correlated with genes related to terpenoid biosynthesis. The combined treatment of drought stress and ABA resulted in a significant reduction of the stress hormone jasmonic acid and an increase of its biosynthetic precursor, OPDA (cis-12-oxophytodienoic acid), in all species. The present research results indicate that ABA treatment at moderate concentrations could be used as a measure to increase the production of some pharmaceutically active phenolic monoterpenes in T. vulgaris, T. serpyllum and T. kotschyanus and increase the stress resistance of the plants.